2013
DOI: 10.1158/1078-0432.ccr-13-0601
|View full text |Cite
|
Sign up to set email alerts
|

microRNA 223 Is Upregulated in the Multistep Progression of Barrett's Esophagus and Modulates Sensitivity to Chemotherapy by Targeting PARP1

Abstract: PURPOSE Recent microarray and RNA-sequencing studies have uncovered aberrantly expressed microRNAs (miRs)in Barrett’s esophagus (BE)-associated esophageal adenocarcinoma (EAC). The functional significance of these miRs in EAC initiation and progression is largely unknown. EXPERIMENTAL DESIGN Expression levels of miR-199a/b-3p, −199a-5p, −199b-5p, −200b, −200c, −223, and −375 were determined in microdissected tissues from cardiac mucosa, BE, dysplastic BE, and EAC using quantitative real time PCR. MiR-223 exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…In addition, in esophageal cancer cells, PARP-1 was identified as a direct target gene of miR-223 (34). Indeed, in esophageal adenocarcinoma cells, decreased cancer growth was observed in cells with enforced miR-223 expression and subsequent reduced PARP-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in esophageal cancer cells, PARP-1 was identified as a direct target gene of miR-223 (34). Indeed, in esophageal adenocarcinoma cells, decreased cancer growth was observed in cells with enforced miR-223 expression and subsequent reduced PARP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, miR-223 was first described as a key player in regulating inflammation in many inflammation-related disorders including DNA damage (11,34,39). Thus, decreased expression in miR-223 in PAH might also play a role in the inflammatory processes by regulating hematopoietic cell differentiation and cytokine production (11), such as IL-6 (6), which also plays a critical role in PAH via STAT3 (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, miR-223 was found to have a tumor suppressor function by inhibiting migration and invasion through targeting Artemin, a tumor metastasis-related gene, in human esophageal carcinoma [178]. In line with this notion, it has been shown that miR-223 is overexpressed in the multiple step progression of Barrett's esophagus and modulates drug resistance via targeting PARR1 [179]. Interestingly, in a separate report, down-regulation of miR-223 was identified in hepatocellular carcinoma, while re-expression of miR-223 caused an inhibitory effect on cell viability in hepatocellular carcinoma cell lines [180].…”
Section: Regulation Of Fbw7 By Mir-223mentioning
confidence: 82%
“…MiR-196a, which is described as a marker of progression from BE to EAC, can increase cell proliferation and anchorage-independent growth and inhibit apoptosis in EAC cell lines in vitro (281). The down-stream target for miR-196a are verified to be Annexin A1, S100 and JHesoAD1 showed more aggressive phenotype and also showed higher sensitivity for DNAdamaging agents (292).…”
Section: Micrornamentioning
confidence: 93%